CONTENT OF TUTORING PROGRAMS IN ABROAD EDUCATION AND POSSIBILITIES OF USING THEM (Scientific journal of the Fergana State University, 2024)
This article covers information and explanations on one of the new systems reformed in our country, the tutoring activity and its impact on the quality of higher education, its advantages, and the extent to which it contributes to students being educated and successful. These will be covered based on the analysis of foreign experience, in particular, researches conducted in Portuguese universities. As a result of these researches, we can witness that a tutor is not only a teacher for a student, but also a person who is ready to be together and work in many other conditions, a motivator, an educator, an observer, a guide, a protector and an encourager. The tariffs of the introduced programs are explained in detail, and the qualities that the tutors who participated in the study should have more are determined based on a questionnaire from the participating students, and through this, it is possible to increase the effectiveness of using the programs in the tutor's work.